ANALISIS DINAMIKA KELOMPOK WANITA PADA KEGIATAN PEMBERDAYAAN KELOMPOK WANITA MELALUI KEWIRAUSAHAAN AGRIBISNIS DI DAS JRATUNSELUNA KABUPATEN GROBOGAN - Dwiningtyas Padmaningrum (AGRITEXTS: Journal of Agricultural Extension, 2004)
Women is potentially human resources for rural development. Their productivity can be developed by rural women groups empowerment activities. This activities can be directed to agribusiness that based on locally natural resources. In this case, the participation of member's group are need to reachout the group's goals. The beginning potential resources of women group must be understood by identifying of group's dynamics, because it's necessary to decide an exact agribusiness activities. The result of this identifying shows that the women groups at sub district of Godong and Geyer have precisely dynamic. Their member's group need some productive enterprises.